Effects of Dietary L-Theanine on Growth Performance, Antioxidation, Meat Quality, and Intestinal Microflora in White Feather Broilers With Acute Oxidative Stress - Wang, Zixi; Tang, Yanfang; Long, Lina; Zhang, Huihua (Frontiers in Veterinary Science, 2022)
In order to reduce the negative effects caused by oxidative stress on broilers, it is particularly important to find ways to alleviate oxidative stress. As a natural plant extract, L-theanine has a variety of biological effects, such as improving antioxidant capacity, promoting growth, and enhancing immunity and antitumor. This trial evaluated the effects of dietary supplementation of L-theanine on growth performance, antioxidation, meat quality, and intestinal microflora in 817 White Feather Broilers. A total of 108 21-day-old 817 broilers with similar body weight (BW) were randomly divided into three groups with six replicates per group and six chickens within each replicate. The three groups were corn-soybean-based diet (NC group); basal diet plus drinking water with 30 mg hydrocortisone/kg (PC group); and basal diet supplemented with 400 mg L-theanine/kg plus drinking water with 30 mg hydrocortisone/kg (LT group). Compared with the NC group, from 21 to 24 days of age, the PC and LT groups had decreased BW, average daily gain (ADG), and average daily feed intake (ADFI), and increased feed to gain ratio (F/G; p < 0.05). At 24 days of age, the LT group had improved superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in serum as compared to the NC group (p < 0.05). The LT group broilers also had significantly higher concentrations of malondialdehyde (MDA) in serum and liver (p < 0.05). On the 42nd days, the PC group had lower PH45min (p < 0.05) than the NC and LT groups and higher cooking loss and shear force (p < 0.05). Moreover, the villi height of the PC group was significantly lower in jejunum than the NC group (p < 0.05). The LT group had a higher ZO-1 content in duodenum than the NC and PC groups (p < 0.05). The activity of GSH-Px in the liver of the LT group was increased than in the PC group (p < 0.05). The relative abundance of Firmicutes in the LT group was significantly higher than in the NC and PC groups (p < 0.05). These results suggested that the effects of acute oxidative stress on growth performance and meat quality of broilers are continuous, and dietary supplementation of L-theanine could improve the growth performance and meat quality, enhance the intestinal mucosal barrier and antioxidant capacity, and improve the composition of the intestinal flora of broilers caused by acute oxidative stress.